MOTIVASI DAN KINERJA KADER POSYANDU (STUDI LITERATUR REVIEW) - Lucia Retnowati; Nurul Pujiastuti; Kasiati (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2022)
Health development is important in the development of human quality in a country. One of the efforts made by the government is to establish Community Based Health Efforts (UKBM) which are managed from, by, for, and with the community, which are useful in empowering the community and providing convenience to the community in obtaining basic health services. One form of UKMB is integrated service post (posyandu). Cadres have an important role in implementing the posyandu program because cadres are in charge. The performance of cadres is a factor in the success of posyandu, with high motivation in posyandu activities so as to improve the performance of posyandu cadres. From the database used, namely Google Scholar, 5 journals were found. The 5 journals used an analytical survey research design with a cross sectional approach published between 2016-2020. The inclusion criteria used were respondents with posyandu cadres. In addition, it is also seen from the completeness of the text, title, abstract, and methodology assessed for the feasibility of the study.Researchers found 5 journals that met the inclusion criteria. The results of these 5 journals show that there is a relationship between motivation and the performance of posyandu cadres. This literature review shows that the motivation and performance of cadres affect the implementation of posyandu.Based on the results of a literature search, it shows that there is a relationship between motivation and the performance of posyandu cadres. This can be proven by the five articles that have been researched showing that the better a person's motivation, the greater the responsibility they have, so that cadres become more active in carrying out posyandu activities.